Antimicrobial application on CHALUA, a Vietnamese sausage - Talan, Ceri Kristine H.
ABSTRACT Cha lua, a Vietnamese sausage, is a famous delicacy with short shelf-life. This study investigated the effects of antimicrobial application to improve the shelf-life of cha lua sausages stored at room temperature. Three antimicrobials were initially tested namely, sodium benzoate, propyl paraben and potassium sorbate. Antimicrobial treated sausages were reported to have lower TPC and YMC counts, indicating inhibitory action. However, potassium sorbate was found to be the most effective antimicrobial, exhibiting the greatest microbial load reduction. Different levels of potassium sorbate were incorporated to cha lua sausages. The maximum allowable concentration of 0.30% was found to have the lowest microbial count and was therefore, the most effective concentration. Sensory quality was not affected at this level of potassium sorbate incorporation. Lastly, the formulation and process for the 0.30% potassium sorbate treated cha lua was standardized.